2007
DOI: 10.1016/j.atmosres.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol remote sensing over land: A comparison of satellite retrievals using different algorithms and instruments

Abstract: An inter-comparison study of the aerosol optical thickness (AOT) at 0.55 μm retrieved using different satellite instruments and algorithms based on the analysis of backscattered solar light is presented for a single scene over central Europe on October 13th, 2005. For the first time comparisons have been performed for as many as six instruments on multiple satellite platforms. Ten different algorithms are briefly discussed and inter-compared. It was found that on the scale of a single pixel there can be large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(112 citation statements)
references
References 45 publications
2
99
0
1
Order By: Relevance
“…In addition to their cloud microphysical effects, aerosols also modulate cloud formation and convective behavior through their radiative effects, for which aerosol optical thickness (AOT) is a commonly used metric. AOT has the advantage of being readily observed by remote sensing, and AOT measurements are now done routinely from space by several sensors (Kaufman et al, 2002;Yu et al, 2003;Kahn et al, 2007;Kokhanovsky et al, 2007) as well as by ground-based sunphotometer networks Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their cloud microphysical effects, aerosols also modulate cloud formation and convective behavior through their radiative effects, for which aerosol optical thickness (AOT) is a commonly used metric. AOT has the advantage of being readily observed by remote sensing, and AOT measurements are now done routinely from space by several sensors (Kaufman et al, 2002;Yu et al, 2003;Kahn et al, 2007;Kokhanovsky et al, 2007) as well as by ground-based sunphotometer networks Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The optimum value of AOT and aerosol model is selected on the basis of best-fit of surface reflectances to the model implemented in the algorithm (North et al, 1999;North 2002), and adapted for efficient processing of global data by Grey et al (2006a). Global validation with AERONET and other satellite sensors was presented by Grey (2006b) and Kokhanovsky et al (2007). The algorithm has also been adapted to use the 5-angle sampling of the CHRIS-PROBA instrument (Davies et al, 2010).…”
Section: Swansea University Algorithmmentioning
confidence: 99%
“…The advances and problems related to aerosol remote sensing from space have recently been reviewed (Kokhanovsky and de Leeuw, 2009;Lee et al, 2009). In particular, it was found that different algorithms/instruments produce somewhat different results for AOT absolute values and spatial distributions even if the same location at the same time is observed Kokhanovsky et al, 2007;Liu and Mishchenko, 2008;Mishchenko et al, 2009;Kahn et al, 2009). Li et al (2009) list the following possible reasons for the discrepancy: (1) cloud masking; (2) instrument calibration; (3) treatment of the underlying surface; (4) assumptions on the aerosol model.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, spaceborne platforms are necessary to observe aerosol properties over global or continental scale. A considerable progress has been made to estimate AOD from space-borne platforms in past two decades (Martonchik et al, 1998;Ignatov et al, 2004;Remer et al, 2005Remer et al, , 2008Kokhanovsky et al, 2007;Laszlo et al, 2008;Livingston et al, 2009;Kahn et al, 2010;Tanré et al, 2011;Hsu et al, 2012). However, only few satellite sensors are able to provide AOD over land and the retrieval of other aerosol properties like size distribution, single scattering albedo or refractive-index remains to be a challenging task.…”
Section: Introductionmentioning
confidence: 99%